2017
DOI: 10.1177/1010539517690225
|View full text |Cite
|
Sign up to set email alerts
|

Household Expenditure on Tobacco Consumption in a Poverty-Stricken Rural District in Sri Lanka

Abstract: Tobacco is a determinant of poverty and a barrier for development. Monaragala, a rural, agricultural district, reports the highest poverty-related indicators in southern Sri Lanka. A cross-sectional study was used to describe the household expenditure on tobacco and its association with food- and education-related expenditures at household level. This study used a 4-stage cluster sampling method to recruit a representative sample of 1160 households. Response rate was 98.6%. Median monthly household income was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…A different study of 1144 households in Sri Lanka revealed that while higher income households spent more on tobacco products, they had a lower tobacco expenditure as a percentage of total household expenditure. 13 Similar results were reported in a study conducted in the Russian Federation, Azerbaijan, Georgia, Kazakhstan, Kyrgyzstan, Tajikistan 15 and another in Morocco. 14 Finally, a study of 748 smokers in the USA showed that lower income households spent a higher percentage of their household income on cigarettes.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…A different study of 1144 households in Sri Lanka revealed that while higher income households spent more on tobacco products, they had a lower tobacco expenditure as a percentage of total household expenditure. 13 Similar results were reported in a study conducted in the Russian Federation, Azerbaijan, Georgia, Kazakhstan, Kyrgyzstan, Tajikistan 15 and another in Morocco. 14 Finally, a study of 748 smokers in the USA showed that lower income households spent a higher percentage of their household income on cigarettes.…”
Section: Introductionsupporting
confidence: 83%
“…Our results were consistent with a previous report in the USA 17 and the findings from other countries, although these findings pertained to the general category of tobacco expenditure and not specifically to cigarette expenditure. 13–16 …”
Section: Discussionmentioning
confidence: 99%
“…This may result from differences in the social, economic, and political environment in different parts of China. 23,107,108 First, most of the antitobacco efforts, including tobacco control and prevention as well as the provision and delivery of cessation services, have been implemented in cities with a higher level of socioeconomic development, like those in eastern China. The implementation and supervision of smoking ban policies in eastern China are also better.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated cost of tobacco in low-and middle-income countries is 10% of the student's income, 17 so the money paid for tobacco is diverted from nutrition, education and medical care. 18 According to the Global Adult Tobacco Survey (GATS), around 22 million people (23.0%) in Bangladesh are currently smoking various types of tobacco products. Approximately 12.0% and 26.0% of the overall population aged 15-24 and 25-44 y, respectively, are consuming some form of tobacco.…”
Section: Introductionmentioning
confidence: 99%